PENGARUH PENERAPAN MODEL PEMBELAJARAN AUDITORY INTELLECTUALLY REPETITION (AIR) TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIKA SISWA DI KELAS VIII SMP NEGERI 1 PASIR PENYU - Helma Mustika; Nuri Kinanti (MES: Journal of Mathematics Education and Science, 2018)
Abstract. This research is based on the students' mathematical communication ability at SMP Negeri 1 Pasir Penyu which is still low. To overcome the problem is applied learning model Auditory Intellectually Repetition (AIR). This study aims to determine the ability of students' mathematical communication using the learning model of Auditory Intellectually Repetition (AIR). This research type is quasi experiment research. The research design used was randomized subjects posttest only control group design. The sampling technique used is cluster random sampling. After the sample was taken randomly, the students selected VIII.6 class as experimental class and students of class VIII.5 as the control class. The instrument in this research is a test of students' mathematical communication skill. The data analysis technique used Independent Samples T-Test (t-test) test. Based on hypothesis test results obtained that tcount = 5,065 ttable = 2.002 with (df = 60) and a real level of 5%. Reject H0 if thitung value is ttable. So it can be concluded that the mathematical communication skills of students using the learning model of Auditory Intellectually Repetition (AIR) is better than the students' mathematical communication skills using conventional learning model. Keywords: Auditory Intellectually Repetition (AIR), mathematical communication.